Does Social Forestry Contribute to Farmers’ Income?: A Case Study of Two Mountainous Villages on Java Island, Indonesia - Nakayama, Hitomi; Rustiadi, Ernan; Fauzi, Akhmad (P4W IPB, 2024)
Social Forestry has been implemented in Indonesia to address environmental conservation and poverty alleviation. However, the effectiveness of this initiative in increasing household income is often subject to scrutiny. This study examines the impact of Social Forestry on household income by comparing Social Forestry members and non-members in two mountainous villages on Java Island. Specifically, the analysis focuses on household surveys conducted in Tombo village in Central Java and Cibulao sub-village in West Java. A negative correlation between membership and household income is observed in Tombo, whereas a positive correlation between membership and farm income is observed in Cibulao. Considering these findings, we posit that pre-implementation land tenure and accessibility may affect the economic outcomes of the program.